2015
DOI: 10.1093/jrr/rrv021
|View full text |Cite
|
Sign up to set email alerts
|

Radio-sensitization effect of an mTOR inhibitor, temsirolimus, on lung adenocarcinoma A549 cells under normoxic and hypoxic conditions

Abstract: The mammalian target of rapamycin (mTOR) correlates with cell survival under hypoxia and regulates hypoxia-inducible factor-1α (HIF-1α), a key protein in hypoxia-related events. However, the role of mTOR in radio-resistance has not been fully investigated. Therefore, the effect of mTOR on the radio-resistance of cancer cells under hypoxia was evaluated using the mTOR inhibitor temsirolimus. Clonogenic survival was examined in the A549 human lung adenocarcinoma cell line under normoxia or hypoxia, with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The right‐hand side of the graph depicts the surviving fractions after the irradiation with an X‐ray dose of 6 Gy. The surviving fraction for X‐rays alone was about 15%, which is in accordance with the literature for A549 cells . The NP concentration of 1.0 mg mL −1 resulted in a decrease of the surviving fraction to 9%.…”
Section: Resultssupporting
confidence: 90%
“…The right‐hand side of the graph depicts the surviving fractions after the irradiation with an X‐ray dose of 6 Gy. The surviving fraction for X‐rays alone was about 15%, which is in accordance with the literature for A549 cells . The NP concentration of 1.0 mg mL −1 resulted in a decrease of the surviving fraction to 9%.…”
Section: Resultssupporting
confidence: 90%
“…Temsirolimus is an intravenous drug for the treatment of renal cell carcinoma and approved by the FDA in late May 2007 [ 109 ]. Temsirolimus binds to an intracellular protein (FKBP-12), and the protein-drug complex inhibits the activity of mTOR that controls cell division [ 110 ]. Yeo et al conducted a study to determine dose limiting toxicity and maximum tolerated dose of temsirolimus in HCC patients in phase I and to assess antitumor activity of temsirolimus in phase II [ 111 ].…”
Section: Targeted Therapies For Hccmentioning
confidence: 99%
“…The blockade of the mTORC1 can activate the ULK1 complex and promote the interaction with the PtdIns3K complex which is necessary for the formation of new autophagosomes (47). Several studies have reported on the positive effects of mTOR inhibitor on sensitizing cancers to radiation therapy and chemotherapy in lung cancer, pancreatic carcinoma cells and esophageal carcinoma cells (48)(49)(50)(51).…”
Section: Dna Damage Repair and Autophagymentioning
confidence: 99%